Інтегральна методика оцінки розвитку організаційної культури підприємств (за результатами експертного опитування) - Ринкевич, Н.С. (Вісник економічної науки України, 2019)
На даний час організаційна культура посідає провідне місце в системі менеджменту підприємства. Мета даного дослідження полягає в удосконаленні методики оцінки розвитку організаційної культури підприємств та її апробації на прикладі українських підприємств з надання транспортних, консалтингових і банківських послуг. У результаті дослідження складено анкету з 24 тверджень, що стосуються особливостей організаційної культури підприємств, і на цій основі здійснено аналіз та оцінювання організаційної культури. Розраховано рівень надійності результатів анкетування за допомогою коефіцієнта Альфа Кронбаха і XYZ-аналізу. Запропоновано інтегральну методику оцінки розвитку організаційної культури підприємств. Апробація даної методики показала, що обстежені підприємства мають середній рівень розвитку організаційної культури, оскільки значення інтегральних показників знаходяться в межах 0,5–0,75. В настоящее время организационная культура занимает ведущее место в системе менеджмента предприятия. Цель данного исследования заключается в совершенствовании методики оценки развития организационной культуры предприятий и ее апробации на примере украинских предприятий по предоставлению транспортных, консалтинговых и банковских услуг. В результате исследования составлена анкета из 24 утверждений, касающихся особенностей организационной культуры предприятий, и на этой основе осуществлен анализ и оценка организационной культуры. Рассчитан уровень надежности результатов анкетирования с помощью коэффициента Альфа Кронбаха и XYZ-анализа. Предложена интегральная методика оценки развития организационной культуры предприятий. Апробация данной методики показала, что исследуемые предприятия имеют средний уровень развития организационной культуры, поскольку значения интегральных показателей находятся в пределах 0,5-0,75. At present, organizational culture has a leading position in the enterprise management system. The purpose of this study is to improve the methodology for assessing the development of organizational culture of enterprises and its testing on the example of Ukrainian enterprises in the provision of transport, consulting and banking services. As a result of the research, a questionnaire was made of 24 statements concerning the peculiarities of the organizational culture of enterprises, and on this basis an analysis and evaluation of the organizational culture was carried out. The reliability of the survey results was calculated using the Alpha Cronbach coefficient and XYZ-analysis. The integrated method of estimation of development of organizational culture of the enterprises is offered. The testing of this methodology showed that the surveyed enterprises have an average level of development of organizational culture, since the values of the integral indicators are in the range of 0.5–0.75. Based on the mentioned above, it is essential to propose priority directions to improve the management of enterprises’ organizational culture development: the application of a customer-oriented approach to the formation of organizational culture, based on the customer focus, complemented by the cross-functional interaction of company human resources in the decision-making process; development and realization: the mechanism of the strategic management of the enterprise organizational culture development; marketing strategy of the enterprise organizational culture development; organizational and economic mechanism for enterprise organizational culture development managing; the complex of measures for the digital transformation of enterprises organizational culture, which includes: use of employee-driven management, that is, an HR oriented approach to management – continuous employees training and skills development halves the time of a new product launching on the market; implementation of HRmaps the next generation modular platform for HR management – a comprehensive solution for the HR processes automation, which consists of 4 modules and the HR portal (personnel assessment; recruitment and adaptation; planning and career; training and development); HR digital upgrade, which is based on the introduction of a digital cloud platform providing a digital format for all personnel processes (up to 90% automation), which allows monitoring and company development. The practical value of the study is that the proposed methodical approach can be used in the activities of enterprises in assessing the level of development of their organizational culture.